If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 3 = 2x + -7 + x Reorder the terms: 3 + 4x = 2x + -7 + x Reorder the terms: 3 + 4x = -7 + 2x + x Combine like terms: 2x + x = 3x 3 + 4x = -7 + 3x Solving 3 + 4x = -7 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 3 + 4x + -3x = -7 + 3x + -3x Combine like terms: 4x + -3x = 1x 3 + 1x = -7 + 3x + -3x Combine like terms: 3x + -3x = 0 3 + 1x = -7 + 0 3 + 1x = -7 Add '-3' to each side of the equation. 3 + -3 + 1x = -7 + -3 Combine like terms: 3 + -3 = 0 0 + 1x = -7 + -3 1x = -7 + -3 Combine like terms: -7 + -3 = -10 1x = -10 Divide each side by '1'. x = -10 Simplifying x = -10
| 7.5m=-60 | | 10x-4=9x+17 | | 3(2a-4)=-12 | | 4x^2-x/2x-1=9 | | 8.5y=-59.5 | | -2x-3x=-25 | | 2(-10-3x)=-38 | | 2(-2)2=8 | | 2/9m=6 | | 14xcubed-68xsquared-10x=0 | | F=9/5k-459.67 | | 6.2+5-1.4=4.8+5 | | 3x+2y+z=50 | | 2/7s=6 | | 2p/3+26=22 | | 10=x/8 | | 4x-1=7x-13 | | 8z-16=4z | | 3x+16=10x+(-12) | | 16z-36=4z | | 6(7x+2)=-324 | | 2(3x-1)=4x+1 | | 16x+12y=20 | | 2x-13=2x-2 | | 6d+3d-3d+6=5d | | 34=1.7x | | 5(2x+3)=7(x+1) | | 7a=0.21 | | 3x+16=10x-12 | | 7x-4=3x+6 | | -5(4+6x)=340 | | 9(1.8x+2)=13.8+30 |